Growing futures: integrating hydroponic and agropreneurship at UiTM Sabah / Nur Aziemah Jasni ... [et al.] - Jasni, Nur Aziemah; Fitri Said, Rozlianah; Sinong, Grace Flavyeliz; Sisa, Mohd Hafezan; Shah, Aloysius Sekui@Mohd Zul Ikhwan (Universiti Teknologi MARA, Kedah, 2024)
This proposal outlines establishing the hydroponics project business for the Diploma in Agropreneurship, Faculty of Plantation and Agrotechnology (FPA), Universiti Teknologi MARA Sabah Branch (UiTMCSH). This project focuses on creating agropreneur‘s fundraising through hydroponic salad cultivation. The fundraising project offers various premium quality salads and promotes agriculture education sustainable practices in salad cultivation. The proposal highlights the unique selling proposition, including providing first-hand experience in salad harvesting, sustainable hydroponic systems, educational opportunities, and subscription services. The target customers of this project include students and staff of UiTMCSH, visitors, cafeterias, and the Hospitality and Tourism Training Center (HTTC), UiTMCSH. In addition, this project teaches students entrepreneurship skills while promoting sustainable agriculture, and the profits generated are used to fund various fundraising projects that continue in semester two forward throughout their study. All collected funding benefits the students for their international academic visit in their fourth semester.